Molecular mechanisms involved in the IL-6-mediated upregulation of indoleamine 2,3-dioxygenase 1 (IDO1) expression in the chorionic villi and decidua of women in early pregnancy - Rui Wang; Shuyun Zhao; Xiaojuan Chen; Ziwen Xiao; Xinghui Wen; Xingming Zhong; Shixiang Li; Hui Cheng; Guanyou Huang (BMC, 2022)
Abstract Background IL-6 induces the upregulation of indoleamine 2,3-dioxygenase (IDO1) at the maternal-foetal interface, but the regulation mechanisms of IDO1 by IL-6 at this interface have not been fully understood. Methods Western blotting, qRT-PCR and/or immunohistochemistry were employed to measure the expression of IDO1, IL-6, SHP-1/2, SOCS3 and STAT3/p (STAT3 and pSTAT3) in tissues of chorionic villi and decidua (TCVD) in vivo and in cultured TCVD that were treated with IL-6 in the presence or absence of an IL-6 inhibitor. Results Mutually positive relationships among the protein levels of IL-6, IDO1, SHP-1/2 and STAT3/p was observed, and the expression of IDO1, SHP-1/2 and STAT3/p was increased in a dose-dependent manner in TCVD in vivo and in cultured TCVD treated with IL-6 at increasing concentrations (0-100 ng/ml). The level of IL-6 was negatively related to SOCS3 level in TCVD. The expression of SOCS3 was increased in a dose-dependent manner, and SOCS3 level was positively correlated with SHP-1, SHP-2 and STAT3/p level in cultured TCVD treated with 0-2 ng/ml IL-6; however, opposite results were observed after treatment with 2-100 ng/ml IL-6. The IL-6-induced upregulation of IDO1, SHP-1, SHP-2 and STAT3/p expression could be reversed, while the IL-6-induced upregulation of SOCS3 expression was exacerbated by Corylifol A. Conclusions In normal pregnancy, IL-6 upregulates the expression of IDO1 by promoting SHP-1/2 expression via STAT3/p and simultaneously negatively regulates the expression of SOCS3. High expression of IL-6 causes the upregulation of IDO1 expression and the downregulation of SOCS-3 expression, which may be beneficial for maintaining immunological tolerance.